Pengaruh penggantian sebagian ransum dengan tepung daun dan batang ubi jalar terhadap kecernaan kalsium dan fosfor pada ternak babi - Bawole, D.A.C.; Rahasia, C.A.; Pontoh, C.J. (Universitas Sam Ratulangi, 2021)
EFFECT OF PART SUBSTITUTION OF DIET WITH LEAF AND STEM OF SWEET POTATO MEAL ON DIGESTIBILITY OF CALCIUM AND PHOSPHOR IN PIG.This study aims to find out the extent of the influence of the use of leaf and stem of sweet potato meal replacing some of the diet on calcium and phosphor consumption and digestibility in pig. This study used the design of latin square (Latin Squere Design) 5 x 5 consisting of 5 male pigs kastrasi results of the crossing Duroc X Spotted Polland China aged about 3.5 - 4.0 months, initial weight 50 kg (± 2.5 kg) and allocated into 5 treatments as follows: R0 = 100% basal diet + 0% leaves and stems of sweet potato; R1 = 92.5% basal diet + 75% sweet potato leaves and stems; R2 = 85% basal diet + 15% leaves and stems of sweet Potatoes, R3 = 77.5% basal diet + 22.5% leaves and stems of sweet potatoes; R4= 70% basal diet + 30% leaves and stems of sweet potatoes.The parameters measured were: the consumption of calcium and phosphorus, as well as theingest of calcium and phosphor. The results showed that the average calcium consumption of pigs in the initial phase of the finisher in each treatment ranged from 10.88 - 13.60grams, and for the average consumption of phosphorus ranged from 10.74% - 13.42grams.While the calcium ingest of pigs early phase finisher in each treatment ranges from 54.37 – 55.16% and for average of phosphor digestibility ranges from 62.27 – 61.23%. The analysis of varian showed that there was no significant difference (P>0.05) each treatmentson to consumption and digestibility of calcium and phosphor. In conclusion, The flour of leaf and stem sweet potato can replace up to 30% of the basic ration of pigs in the initial phase of finisher no negative effects on consumption of digestibility calcium and phosphor.Keywords: Leaves and stems of sweet potatoes, ingested calcium phosphorus, pig livestock